A self-assembling nanomaterial reduces acute brain injury and enhances functional recovery in a rat model of intracerebral hemorrhage - Sang, Lynn Yan-Hua; Ellis-Behnke, Rutledge (Nanomedicine. Nanotechnology, biology and medicine, 2015)
There is no effective treatment for intracerebral hemorrhage (ICH). Intracerebral delivery of nanomaterials into the hemorrhagic lesion may be a new therapeutic strategy. In a rat model of ICH plus ultra-early hematoma aspiration, we found that locally delivered self-assembling peptide nanofiber scaffold (SAPNS) replaced the hematoma, reduced acute brain injury and brain cavity formation, and improved sensorimotor functional recovery. SAPNS serves as biocompatible material in the hemorrhagic brain cavity. Local delivery of this nanomaterial may facilitate the repair of ICH related brain injury and functional recovery. From the Clinical Editor: In a rat model of intracranial hemorrhage, these authors demonstrate that following ultra-early hematoma aspiration, local delivery of a self-assembling peptide nanofiber scaffold replaces the hematoma, reduces brain cavity formation, and improves sensorimotor functional recovery. Similar approaches would be welcome additions to the clinical treatment of this often devastating condition.